2023
DOI: 10.1101/2023.07.06.548005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abscisic acid inhibits germination of Striga seeds and is released by them as a rhizospheric signal providing competitive advantage and supporting host infestation

Abstract: Seeds of the root parasitic plant Striga hermonthica undergo a conditioning process under humid and warm environments before germinating in response to host-released stimulants, particularly strigolactones (SLs). The plant hormone abscisic acid (ABA) regulates different growth and developmental processes, and stress response; however, its role during Striga seed germination and early interactions with host plants is under-investigated. Here, we show that ABA inhibited Striga seed germination and that hindering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For instance, it was recently shown that, upon germination, Striga seeds release abscisic acid that negatively impacts the conditioning and germination of neighbor seeds under laboratory conditions. 28 On the other hand, SL-induced germination in Striga spp. led to the production of ethylene.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was recently shown that, upon germination, Striga seeds release abscisic acid that negatively impacts the conditioning and germination of neighbor seeds under laboratory conditions. 28 On the other hand, SL-induced germination in Striga spp. led to the production of ethylene.…”
Section: Discussionmentioning
confidence: 99%